Teacher Professional Development around the World : The Gap between Evidence and Practice - Popova, Anna; Evans, David K.; Breeding, Mary E.; Arancibia, Violeta (World Bank, Washington, DC, 2018)
Teachers, like all professionals, require ongoing professional development opportunities to improve their skills. This paper provides evidence on effective professional development characteristics and how at-scale programs incorporate those characteristics. The authors propose a standard set of 70 indicators—the In-Service Teacher Training Survey Instrument—for reporting on professional development programs as a prerequisite for understanding the characteristics of those programs that improve student learning. The authors apply the instrument to rigorously evaluated professional development programs in low- and middle-income countries. Across 33 programs, those programs that link participation to career incentives, have a specific subject focus, incorporate lesson enactment in the training, and include initial face-to-face training tend to show higher student learning gains. In qualitative interviews, program implementers also report follow-up visits as among the most effective characteristics of their professional development programs. The authors then apply the instruments to a sample of 139 government-funded, at-scale professional development programs across 14 countries. This analysis uncovers a sharp gap between the characteristics of teacher professional development programs that evidence suggests are effective and the global realities of most teacher professional development programs.